PRINCIPLES OF FINANCING THE EDUCATION SYSTEM - Dusanov Salim Mamarasulovich (Bright Mind Publishing, 2025)
The article describes financial resources, financing issues, problems and their importance in the education system. At the same time, analytical approaches to the effectiveness of financial resources of educational institutions and theoretical and methodological foundations for its study are presented.
Keywords: Education system, financing, state of financing, problems and effectiveness of financial resources, effective management of educational institutions, rating, financial stability, solvency, profitability